Política de Ciência e Tecnologia no Amazonas: a perspectiva de inclusão do Programa Ciência na Escola da FAPEAM - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This current study discuss the perspective of including the science and technology from the “Programa Ciência na Escola – PCE” of “Fundação de Amparo” to “Pesquisa do Estado do Amazonas”, centered on the scientific formation of public school students at the state of Amazonas through research projects carried out within school. Our purpose was to verify in each sense the science and technology is a key factor to human and social development, emphasizing in this scenario the Science Program at School of FAPEAM. The methodology followed the guidelines of qualitative approaches without deleting the quantitative aspects. The fieldwork was conducted based upon the official documents of FAPEAM as minutes, reports, publications, journals, articles, sites, and extraction of reports of authorities at magazines. We performed the analysis of the effects and positive results arising from the inclusion of youth and adults in the system of science and technology, as well as we point out the difficulties and anxieties of the main individuals involved in the program, who are students and teachers. It became evident the fact that program participants consider that there is an important contribution from the PCE for they learning and studying process, and for the development of new knowledge coming through that experience of scientific research. The Scientific Initiation can mean for teachers and students of basic education a relevant contribution to continuing education. The learning constructed through the act of researching / investigating can lead a change in teaching practice, which certainly will be a reference for the procedure for changes in quality of education at the state of Amazonas.
Keywords: .; .; .; CIENCIAS HUMANAS; Cultura Científica; Educação Científica; Política de Ciência e Tecnologia